Adversities in Syria and their relation to their physical and mental health conditions as Syrian refugees in Turkey. (2nd August 2021) - Balcilar, Mehmet; Nugent, Jeffrey B.; Xu, Jiahui
Abstract: The purpose of this paper is to examine the extent to which different health problems among Syrian refugees in Turkey can be traced back to three different conditions in Syria (Family Member Killed, House Damaged, and Income) as well as to Commonality among Neighbors back in Syria as well as in Turkey. As is common, the findings show their effects on mental health to be most common, especially among females, but also that (1) the effects on diseases and physical/mobility problems are also quite significant, (2) in most cases, the effects of income in Syria on Health adversities are positive, and (3) that some of these adverse effects have been growing over time since fleeing Syria.